LINGUACULTURAL APPROACHES TO TEACHING FOREIGN LANGUAGES AS A SECOND LANGUAGE (Web of Teachers: Inderscience Research, 2024)
This article explores the linguacultural approach in teaching foreign languages as a second language, emphasizing the interplay between language and culture. It examines methods such as culturally embedded instruction, comparative cultural analysis, and the use of authentic materials to enhance learners’ cultural competence. The findings highlight how integrating linguacultural elements not only facilitates language acquisition but also deepens learners’ intercultural awareness, making communication more effective and meaningful.